Digital Divide: From a Peripheral to a Core Issue for all SDGs - Valdez, Violet B (Archīum Ateneo, 2020)
The term “digital divide” refers to the disparities that separate segments of society and nations into those who have and those who do not have digital access; skills; and knowledge; which lead to differences in digital use; opportunities; and benefits. Initially the phenomenon was thought of as a problem of access; i.e.; the divide that separates those who have access to information and communications technologies (ICT) and those who do not. As the issue came to be linked with social inequality; the understanding of the concept shifted to a focus on the different types; levels; and outcomes of digital use. In current research; the digital divide is viewed along three levels. The first-level digital divide involves differences in basic physical and material access. Physical access refers to access to computer devices while material access refers to access to the means to purchase Internet connectivity services. These types of access vary among individuals and groups along sociodemographic lines such as gender; age or generation; occupation; and ethnicity. Similarly; the international access divide lies along lines of wealth and privilege. As access to ICT became more prevalent; the discourse shifted from the access divide to the skills divide. This is termed the second-level digital divide and refers to the gap that separates those individuals and groups who possess the set of skills needed to use ICT in beneficial ways from those who do not possess such skills. Further research would show the existence of a third-level divide – the gap among individuals and groups in terms of the outcomes that ICTs bring to their offline lives; e.g.; in their participation in political; social; and educational activities. The fast and widespread diffusion of smartphones worldwide has led to new forms of digital divide; such as a knowledge gap.